2017
DOI: 10.5539/jas.v9n4p21
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Live Yeast Supplementation on Beef Cattle Performance: A Systematic Review and Meta-Analysis

Abstract: This meta-analysis evaluates the effects of yeast supplementation (Saccharomyces cerevisiae) on dry matter intake (DMI) and average daily gain (ADG) in beef cattle. The inclusion criteria were complete and randomized trials and supplementation with yeast S. cerevisiae versus no supplementation to measure DMI or ADG. Data were extracted from relevant papers via pre-defined protocols. A meta-analysis of random effects was conducted for each indicator separately including the mean of the control and treated group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 36 publications
3
23
0
4
Order By: Relevance
“…In present study, cattle fed low plane of nutrition diet supplemented with ADY 4 g/head/d significantly increased ADG, and achieved to a comparable level with cattle fed with high plane of nutrition diet, which was in agreement with the research of Geng et al [18]. Previous studies have shown that the supplementation with ADY could increase ruminant animals DMI [19], however there were also some studies showed that DMI could be reduced [20,21]. Our results indicated that dietary supplementation with ADY had no significant effect on DMI, which was consistent with the result reported by Vyas et al [22].…”
Section: Discussionsupporting
confidence: 92%
“…In present study, cattle fed low plane of nutrition diet supplemented with ADY 4 g/head/d significantly increased ADG, and achieved to a comparable level with cattle fed with high plane of nutrition diet, which was in agreement with the research of Geng et al [18]. Previous studies have shown that the supplementation with ADY could increase ruminant animals DMI [19], however there were also some studies showed that DMI could be reduced [20,21]. Our results indicated that dietary supplementation with ADY had no significant effect on DMI, which was consistent with the result reported by Vyas et al [22].…”
Section: Discussionsupporting
confidence: 92%
“…Yeast cell viability can be reduced during production, storage, and delivery as well as by the ruminal environment such as low pH when cattle are fed high-grain diets. Thus responses to ADY have been variable when it was used in animal studies (Sullivan and Bradford, 2011;Sartori et al, 2017). Fratianni et al (2014) found dramatic loss of yeast cell viability after 4 wk of storage at 4 °C, Table 3.…”
Section: Survival Of Edy Under Simulated Gastrointestinal Conditionsmentioning
confidence: 99%
“…Feed intake responses of beef cattle to live yeast (LY) supplementation have been variable; some studies reported increased DMI (Robinson, 2010;Habeeb, 2017), whereas, other studies stated a reduction of DMI (Rodrigues et al, 2013;Sartori et al, 2017). Furthermore, there appears to be more studies that report no impact of LY supplementation on DMI than studies that report positive or negative effects (Beauchemin, 2012).…”
Section: Effect Of Yeast Supplementation On Growth Performance and Camentioning
confidence: 99%
See 1 more Smart Citation
“…Os frequentes incrementos dos custos da suplementação da dieta dos animais têm estimulado o interesse pelo aproveitamento de alimentos não convencionais na indústria de alimentação animal do Brasil (MONÇÃO et al, 2016a). Dentre os produtos que apresentam potencial de substituir os suplementos proteicos, por exemplo, e suprir os nutrientes deficientes nos pastos, destacam-se as algas, fungos filamentosos e, principalmente, leveduras obtidas a partir da fermentação da cevada e da cana-de-açúcar, considerados fonte de proteínas, além de apresentarem rápido crescimento e possibilidade de cultivo em vários tipos de substratos (SARTORI et al, 2017). ISSN: 2318-356X V.6 N.2 MAI/AGO 2018 A exploração desses microrganismos tornou-se evidente a partir da Segunda Guerra Mundial, época em que se tornaram escassos os alimentos ricos em proteínas e vitaminas.…”
Section: A Introduçãounclassified